<span>b^4 − b^3 + b − 1
=(</span><span>b^4 − b^3) + (b − 1)
= b^3(b - 1) + (b - 1)
=(b - 1)(b^3 + 1)</span>
1 ft= 12 inches
1/2 ft= 6 inches
=3 1/2 feet - 6 inches
substitute # of inches in for 1/2 foot
=3 ft 6 inches - 6 inches
=3 feet
ANSWER: 3 feet
Hope this helps! :)
Answer: Hello, Ascending Order. Ascending Order. Arranging numbers (or other items) in ascending order means to arrange them from smallest to largest. Example 1 (with Numbers) The numbers 12, 5, 7, 10, 1, 160 arranged in ascending order are 1, 5, 7, 10, 12, 160.
Step-by-step explanation:
1: slope = 2/1 or 2
2: slope = 5/-5
3: slope = 3/2
4: slope = 7/-4
5: slope = 3/5
6: slope = 2/-8
7: slope = 6/2 or 3
8: slope = 2/-4
9: slope = 1/6